Ayurvedic Concept of Wellness - Aswathy, P; Aravind, S (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Wellness is the most cherished asset in the living world. A healthy body, healthy mind, healthy soul in a healthy environment is the prime need of every human individual. The Global Wellness Institute defines Wellness as the active pursuit of activities, choices and lifestyles that lead to a state of holistic health. In this era of urbanization and industrialization, man is running behind this busy world which makes him unable to look after his healthy matters. Ayurveda is the science which explains the way of living in harmony with the laws of nature. The aim of this article is to define the concept of wellness according to Ayurvedic and modern approach and the practices that should be followed for wellness. Materials and Methods: The concept of Wellness and practices adopted for the maintenance of wellness according to Ayurveda and modern approach is elucidated through Literature review of classical Ayurvedic books and journalistic reviews. Results and Discussion: Ayurveda can be considered as a science of wellness through its holistic approach and methods adopted for prevention of diseases. Wellness of a person is multidimensional-physical, mental, social, spiritual and emotional. The following practices helps in maintaining wellness such as Dinacharya, (daily regimen) Rithucharya (seasonal routine), Rathricharya, (night regimen) Sadvritta (code of good conduct) Achara Rasayana, (code of conduct), Brahmacharya (Celibacy), Garbhini paricharya (antenatal care) Sutika paricharya, (Post natal Care) Navajatasisu paricharya, (neonatal care) Ritu Sodhana,(seasonal Purification) Aharavidhi (Ayurveda Dietetics), Nidravidhi,(Sleeping order) Control over mental urges and normal evacuation of physical urges, Intake of Rasayana (rejuvenation therapy) and Vajeekarana (Aphrodisiac treatment) avoidance of Prajnaparadha (crime against wisdom)adoption of Yoga and Pranayama, cultivation and propagation of medicinal plants etc.